PENGEMBANGAN MODUL AJAR BERBASIS KEARIFAN LOKAL DENGAN PENDEKATAN MATEMATIKA REALISTIK UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH SISWA - Azlika , Dwi; Ramadhana, Raden Sri Ayu; Rahmat, Defri (Pedagogy: Jurnal Pendidikan Matematika, 2025)
This study aims to develop a local wisdom-based mathematics teaching module with a Realistic Mathematics approach (PMR) to improve students' mathematical problem solving skills on the material of the System of Linear Equations of Two Variables (SPLDV). The background of this research is based on the low results of Indonesia's PISA in 2022 and the findings at MTs Raudlatul Uluum Aek Nabara which show the low problem solving ability of students, as well as the unused teaching materials that link the local cultural context. The research used the Research and Development (R&D) method with the ADDIE model which includes the stages of analysis, design, development, implementation, and evaluation. The research subjects were 38 students of class VIII-D. The results of module validation by experts showed that the module was in the "valid" category (average score 4.69). The results of the student response questionnaire showed that the module was "very practical" with a percentage of 94%. The effectiveness test using N-Gain showed a significant increase in problem solving ability with an average score of 79.66% and all students showed a high increase, so it was categorized as "very effective". Thus, this local wisdom-based module with PMR approach is proven to be valid, practical, and effective to improve students' mathematical problem solving skills.